PENGARUH KELAS LERENG TERHADAP KERAPATAN INDIVIDU DAN PRODUKSI BIOMASSA TUMBUHAN BAWAH DI KHDTK MANDIANGIN - Lisani Nuura Aulia; Yusanto Nugroho; Asysyifa Asysyifa (Universitas Lambung Mangkurat, 2020)
The influence of the slope classes on individual density and the production of biomass of lower plants in KHDTK Mandiangin, with Advised by Dr. Yusanto Nugroho S.Hut, M.P. as the first Adviser and Asysyifa, S.Hut, M.P. as the second Adviser. This research aims to analyze the individual density of various classes of slopes and analyzing the biomass of lower plants on various classes of slopes. The methods used are vegetation analysis, sampling of plants down to the oven process in the laboratory. This research shows that most individual density is found in slope classes 26–45% of 12,36 individual/ha, at least on the slpe class 16-25% sebesar 9,36 individual/ha, on slope class 0-15% of 11,40 individual/ha, and on the top most slope class >45% of 11,40 individual/ha, both slopes have the same amount of individual density butt are different for the amount of vegetation growth the level of seedlings, stakes, poles, and trees on each slope class. The highest biomass production of undergrowth fund on the slope class 0-15% as much as 0,835 ton/ha and the lowest in the >45% slope class of 0,757 ton/ha, on slope class 16-25% as much as 0,771 ton/ha, and on slope class 26-45% as much as 0,768 ton/ha. The increasing grade of the slope will result in the number of individual densities and lower or decreased plant biomass production. Keyword: Classes of slope; individual density; biomass of lower plants